2005
DOI: 10.1080/09603120500155765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of estrogenic activities of pesticides using an in vitro reporter gene assay

Abstract: The estrogenic activities of 32 pesticides in agricultural products were evaluated using the E-CALUX assay system developed by Xenobiotic Detection Systems Inc (North Carolina, USA). This system utilizes human ovarian carcinoma cells (BG1) stably transfected with an estrogen-responsive luciferase reporter gene plasmid. It was found that tolclofos-methyl, prothiofos, diazinon, Thiabenclazole (TBZ) and pyriproxyfen had estrogenic activity. Several pesticides are often present in agricultural products. Therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…With the species steadily declining, despite adequately nutritional support, some other underlying mechanism has to be involved with the poor breeding success of the species. With skeletal abnormalities, poor hatchability and increased hatchling mortalities in other species being blamed on estrogenic effects of low doses of the organochlorines (Grünfeld and Bonefeld-Jorgensen, 2004;Kojima et al, 2005), it is plausible that the poor breeding and rearing success in the Cape Griffon is also due to an underlying endocrine disruptive (ED) syndrome (Bitman et al, 1968;Akins and Tuan, 1993;Danzo, 1997;Sonne et al, 2004;Derfoul et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the species steadily declining, despite adequately nutritional support, some other underlying mechanism has to be involved with the poor breeding success of the species. With skeletal abnormalities, poor hatchability and increased hatchling mortalities in other species being blamed on estrogenic effects of low doses of the organochlorines (Grünfeld and Bonefeld-Jorgensen, 2004;Kojima et al, 2005), it is plausible that the poor breeding and rearing success in the Cape Griffon is also due to an underlying endocrine disruptive (ED) syndrome (Bitman et al, 1968;Akins and Tuan, 1993;Danzo, 1997;Sonne et al, 2004;Derfoul et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being responsive to natural ligands such as estradiol and synthetic estrogens such as diethylstilbestrol, the ERs are also responsive to estrogen-like agrochemicals. The most common of these chemicals are the organochlorines such as DDT and DDE, which are known to be demonstrated innate competitive agonistic activity for ER binding sites (Kojima et al, 2005). Therefore, to ascertain if DDT and DDE could have an adverse effect on vulture reproduction, we sequenced and cloned the vulture ERa from two vulture species, validated an in vitro ER reporter assay prior to determining the influence of p,p 0 -DDT, o,p 0 -DDT and p,p 0 -DDE on receptor transcription activity.…”
Section: Introductionmentioning
confidence: 99%
“…56) Moreover, it has been reported that the PYR metabolites, 3-PBAlc and 3-PBAld, possess estrogenic activity of approximately 10 5 less than that of 17b -estradiol. 57,58) These experimental data, although the tested dose was not necessarily low, could provide a new explanation for some of the findings observed in human studies.…”
Section: Results Unitsmentioning
confidence: 90%
“…Indeed, the lack of consistency in epidemiological and experimental results places these chemicals in EDC category III, a category that includes compounds for which in vitro *Manuscript for revision (track changes hidden) Click here to view linked References data exist but for which data from experimental animals concerning adverse effects on endocrine homeostasis are weak or lacking (Foster and Agzarian, 2008 (Vinggaard., 1999). Imazalil showed weak anti-estrogenic activity in an in vitro gene-reporter assay (Kojima et al, 2005) and a negligible proliferation response in an MCF7 cell proliferation assay . Endosulfan also showed an estrogenic response in several in vitro tests Andersen et al, 2002 (Flynn, 2011).…”
Section: Introductionmentioning
confidence: 99%